Studi Empiris Kekuatan Stabilitas Keuangan Perbankan Syariah di Indonesia - Heniwati, Elok (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2019)
The study aims to examine the stability of Islamic banking in Indonesia after the global financial crisis. This study is significant, considering the rapidly growth of Islamic banking in Indonesia and uniqueness of its operating systems and products. By using secondary data from the annual reports of the banking sector listed on the Indonesia Stock Exchange (IDX) for the period from 2013 to 2016, regression analysis with the ZSCORE function (insolvency risk) as the dependent variable and a number of predictor variables (firm-specific, macroeconomic and governance) are used as tools for achieving research objectives. To check the robustness of the research findings, a model with different specifications has been used. The results indicate that profitability and firm size have a significant influence on the insolvency risk (ZSCORE) of banks and empirical factors that influence these risks differ between Islamic banks and conventional banks.